Readiness of High School Mathematics Teachers in Implementing the 2013 Curriculum in Online Learning - Alim Tarmizi; Rezkiatu Novia Alhikmah (Journal of Research on Mathematics Instruction (JRMI), 2021)
The Covid-19 outbreak that hit Indonesia required teachers to carry out online learning while still prioritizing the quality of education. This study aims to describe the readiness of Mathematics teachers to implement the 2013 curriculum in online learning to create quality learning. This readiness consists of several indicators, namely (1) understanding of the structure and material of the 2013 curriculum mathematics, (2) readiness to use teachers' mathematics books, (3) readiness to use students' mathematics books, (4) readiness to plan mathematics learning, (5) management readiness mathematics learning, (6) the readiness of the mathematics learning process, (7) the readiness of the assessment process. The data collection technique used a questionnaire. The research subjects were all high school mathematics teachers in Tualang District. The data analysis technique used descriptive qualitative. The results showed that the readiness of mathematics teachers at Se- Spectacular Tualang High School to implement the 2013 curriculum in online learning was in the "very unprepared" category of 10% (2 teachers), 25% "unprepared" category (5 teachers), "ready enough" category by 15% (3 teachers), the "ready" category by 40% (8 teachers), and the "very ready" category by 10% (2 teachers). Curriculum 2013 on online learning is included in the "ready" category.